2018
DOI: 10.1111/1471-0528.15148
|View full text |Cite
|
Sign up to set email alerts
|

Foundation for an evidence‐informed algorithm for treating pelvic floor mesh complications: a review

Abstract: Removal of mesh must balance resolution of complications with the risk of removal and recurrence of pelvic floor symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 81 publications
0
17
0
2
Order By: Relevance
“…It seems essential to continue long‐term monitoring after surgical pelvic floor repair, whether mesh is used or not, to ensure comparison and to follow changes in practice as women’s and surgeons’ opinions of mesh evolves . The registry will allow us to compare the different types of materials and the different methods of placement, to identify those that could present problems and to propose guidelines for the prevention and management of these complications and their sequelae . The answers to these questions are of interest to clinicians, women, manufacturers, and the public health authorities.…”
Section: Discussionmentioning
confidence: 99%
“…It seems essential to continue long‐term monitoring after surgical pelvic floor repair, whether mesh is used or not, to ensure comparison and to follow changes in practice as women’s and surgeons’ opinions of mesh evolves . The registry will allow us to compare the different types of materials and the different methods of placement, to identify those that could present problems and to propose guidelines for the prevention and management of these complications and their sequelae . The answers to these questions are of interest to clinicians, women, manufacturers, and the public health authorities.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Lack of careful consideration on appropriate patient selection for surgery may lead to complications and poor outcomes, 24 which have resulted in the development of evidence-informed algorithms for best practice management. 25 The GPAS pathway not only has the potential to reduce the number of review appointments required before conversion to surgery but also ensured that the patients who were accessing this management option were the most appropriate candidates with a greater chance of a successful clinical outcome because of their pre-operative physiotherapy input. 17 Existing research also highlights that up to 25% of women actually complete a counterproductive maneuver, such as straining, when provided with only verbal cues on how to contract the pelvic floor with this issue more commonly observed in women with POP.…”
Section: Discussionmentioning
confidence: 99%
“…The most common first-line surgical treatment was trimming of mesh/ partial excision (51%) followed by complete mesh excision (27%) and release of mesh arms (18%) [30]. A study of > 60,000 retropubic slings in the UK found that 2.2% underwent surgery for mesh removal; the majority (70%) were partial removals [1]. In a small retrospective study comparing complete versus partial mesh removal for mesh exposure, Jambursaria et al found significant recurrent postoperative SUI in 52% of patients with complete mesh removal compared with 25% recurrent SUI in the partial mesh removal group.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(a) A more significant intervention than the partial removal with longer operating time, increased risk of bleeding requiring transfusion (1%) and damage to the urethra or bladder (1%) [1,2]. (b) Risk of incomplete removal especially with retention of one or both tape anchors (10%).…”
mentioning
confidence: 99%
See 1 more Smart Citation